ESSA's student manual for health, exercise & sport assessment - Coombes, Jeff; Skinner, Tina (2014)
ESSA's Student Manual for Health, Exercise and Sport Assessment is an essential text for any student undertaking an exercise and sports science degree and professionals working in the exercise and fitness industries. This practical manual contains fundamental theory and detailed step-by-step protocols designed to assist students and practitioners to develop competency for conducting tests in exercise, health and sports science. Written by leading Australian and New Zealand Academics and published in collaboration with Exercise & Sports Science Australia (ESSA), ESSA's Student Manual for Health, Exercise and Sport Assessment is the first Australian text written with ESSA's accreditation framework in mind.